Intergenerational Justice and the Chain of Obligation. (1st May 1992) - Howarth, Richard B.
The actions and decisions taken by the present generation will affect not only the welfare but also the composition of future generations. A number of authors have used this fact to bolster the conclusion that the present is only weakly obligated to provide for future welfare since in choosing between futures of poverty and abundance, we are not deciding the welfare of a well-defined group of future persons but instead deciding which set of potential persons Ð the poor or the rich Ð will become actual. Provided that future generations have lives that are worth living, they will be grateful to us for bringing them into existence Ð or so the argument goes. In this paper, I argue that this position overlooks an important aspect of the intergenerational problem. We are obligated to provide for the actual children of today, who will in turn be obligated to provide for their children, and so forth from generation to generation. A chain of obligation is thus defined that stretches from the present into the indefinite future, and unless we ensure conditions favourable to the welfare of future generations, we wrong our existing children in the sense that they will be unable to fulfill their obligation to their children while enjoying a favourable way of life themselves.